Real-world study of adverse events associated with gepant use in migraine treatment based on the VigiAccess and U.S. Food and Drug Administration’s adverse event reporting system databases - Liang, Qiaofang; Liao, Xiaolin; Wu, Hongwen; Huang, Yushen; Liang, Taolin; Li, Hailong (Frontiers in Pharmacology, 2024)
Background This study aimed to investigate the real-world profile of adverse events (AEs) associated with gepant medications in the clinical treatment of migraines by analyzing data collected from the VigiAccess database and the U.S. Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database. As novel migraine therapies, gepants act by targeting the calcitonin gene-related peptide (CGRP) pathway, demonstrating effective control of migraine attacks and good tolerability. Nonetheless, comprehensive real-world studies on the safety of gepants are still lacking, particularly regarding their safety in large populations, long-term use, and potential adverse reactions in specific groups, which necessitates further empirical research. Leveraging these two international adverse event reporting system databases, we systematically gathered and analyzed reports of AEs related to gepant medications, such as rimegepant. Our focus encompasses but is not limited to severe, new, and rare adverse reactions induced by the drugs, as well as safety issues pertaining to the gastrointestinal, cardiovascular, hepatic, and renal systems. Through descriptive statistical analyses, we assessed the incidence and characteristics of AEs, compared AEs among gepants, and uncovered previously unknown AE information, all with the goal of providing a reference for the selection of clinical treatment regimens and AE monitoring. Methods By extracting all AE reports concerning “rimegepant”, “atogepant”, and “ubrogepant” from the VigiAccess and FAERS database since its establishment up to 31 March 2024, a retrospective quantitative analysis was conducted. The reporting odds ratio (ROR) method were used to compare AEs among the three gepants. Results In the VigiAccess and FAERS databases, 23542 AE reports in total, respectively, were identified as being related to gepant medications. Among gastrointestinal system AEs, rimegepant had the greatest proportion and greatest signal strength; nausea was most severe and had the strongest signal in rimegepant AEs, whereas constipation was most prominent and had the strongest signal in atogepant AEs. In skin and subcutaneous tissue disorders, rash and pruritus were more frequently observed with rimegepant, followed by ubrogepant. Alopecia emerged as a novel AE, being more severe in rimegepant and secondarily in atogepant. Regarding cardiac disorders, the three gepants showed comparable rates of cardiac AEs, yet rimegepant exhibited the strongest AE signal. In musculoskeletal and connective tissue AEs, ubrogepant presented the most positive signals for skeletal muscle AEs. Furthermore, among the rare blood and lymphatic system disorder AEs, rimegepant had the highest number of reports of Raynaud’s phenomenon and the strongest signal. The study also revealed that while reports of AEs involving liver diseases were scarce across the three gepants, severe AEs were detected in clinical trials, highlighting the need for continued, enhanced monitoring of liver system AEs through large-scale datasets. Conclusion Gepant medications exhibit similarities and differences in their safety profiles. Analysis of the two databases indicated the presence of AEs across various systems, including gastrointestinal disorders, skin and subcutaneous tissue diseases, musculoskeletal and connective tissue disorders, organ-specific effects, and liver diseases. However, each drug displays distinct incidences and signal intensities for these AEs. Additionally, the study revealed a rare AE in the form of Raynaud’s phenomenon. These findings suggest that during clinical use, individualized medication selection and AE monitoring should be based on the patient’s physiological condition and specific characteristics.